Culottes and Warm Pyjamas: Patterns for Home Sewing in Sweden During the Second World War - Törnvall, Gunilla (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2022)
When restrictions and rationing took effect during the Second World War, home sewing became a necessity for many women. This paper presents and discusses the distribution of paper patterns for home sewing in Sweden during the war years, using the examples of three different pattern magazines. It shows how these magazines conveyed, interpreted, and adapted fashion to home sewers. Despite the fact that such periodicals were bestsellers, they have attracted limited scholarly attention both in media history and in the history of reading. This paper highlights the role of print culture in women’s homemade clothes manufacturing and thus contributes to an often‑neglected part of women’s history.